Resisting Hegemony And Defending Chinese Identity In Selected Novels By Malaysian Chinese Writers - Tan, Chye Sing (2010)

(untitled)
The purpose of this study is to find out how the theory of hegemony and various types of hegemonies are applicable in the analysis of the novels. It also focuses on how hegemony and its resistance assist us to understand Chinese identity, especially in the Malaysian context. This theory is used to analyse how the protagonists engage hegemony and its resistance in defending Chinese identity as portrayed in the novels by Malaysian Chinese writers. The four selected novels are Yang-May Ooi’s Mindgame (2000), Chong Seck Chim’s Once Upon a Time in Malaya (2005), Tash Aw’s The Harmony Silk Factory (2005), and Tan Twan Eng’s The Gift of Rain (2007). These novels are chosen because they promote Chinese philosophy, culture and history, which are also embraced by the Chinese protagonists - Fei in Mindgame, Ah Kiew in Once Upon a Time in Malaya, Johny Lim in The Harmony Silk Factory, and Philip Hutton in The Gift of Rain.The study of hegemony is based mainly on Antonio Gramsci’s Selections from the Prison Notebooks, and Hegemony and Socialist Strategy: Towards a Radical Democratic Politics by Ernesto Laclau and Chantal Mouffe, Jonathan Joseph’s Hegemony: A Realist Analysis, as well as Mao Tse-tung’s On Guerilla Warfare, which provide deep insights into how hegemony works and the strategies of resisting it. Hegemony is found in politics, the economy, history, culture, philosophy and even religion in society. The main theory engages constant changes and could be interpreted differently according to the time, political, historical and cultural contexts. The symbiotic relationship between hegemony and other related concepts such as diasporic resistance, difference, and Chinese Communism in resisting ideological, educational and economic hegemonies is discussed. In resisting historical, religious and cultural hegemonies, the hegemonic concepts of revolution, alienation and dislocation are applied and elaborated. By resisting hegemony, the Chinese protagonists in the texts revisit their ancestral roots, Chinese history, religion, culture and language to defend their Chinese identity.